Improved thermal stability and power consumption performances of Ge1Sb9 phase change thin films via doping yttrium. Issue 33 (8th August 2022) - Xu, Shengqing; Wu, Weihua; Gu, Han; Zhou, Xiaochen; Shen, Bo; Zhai, Jiwei
Abstract : Y-doped Ge1 Sb9 thin films have higher crystallization temperature and data retention capacity. Abstract : The effect of yttrium doping on the phase transition properties and crystal structure of Ge1 Sb9 thin films was studied. Y-doped Ge1 Sb9 thin films have higher crystallization temperature (218 °C) and data retention capacity (141.2 °C for 10 years), revealing that Y doping improves amorphous thermal stability. X-ray diffraction and X-ray photoelectron spectroscopy analysis show that the addition of yttrium could inhibit grain growth and restrict the grain size due to the formation of amorphous Y and Ge components. X-ray reflectivity results show that yttrium doping results in less volume change, which predicts the enhanced performance stability of the device. A T-shaped phase change memory cell based on the Y0.26 (Ge1 Sb9 )0.74 films exhibits a faster operation speed (100 ns) and lower power consumption (2.4 × 10 −10 J) than traditional Ge2 Sb2 Te5 materials. The results reveal that Y-doped Ge1 Sb9 is a phase change memory material with good structural properties and device performance.